Local drug delivery for enhancing fracture healing in osteoporotic bone. (1st January 2015) - Kyllönen, Laura; D'Este, Matteo; Alini, Mauro; Eglin, David
Graphical abstract: Abstract: Fragility fractures can cause significant morbidity and mortality in patients with osteoporosis and inflict a considerable medical and socioeconomic burden. Moreover, treatment of an osteoporotic fracture is challenging due to the decreased strength of the surrounding bone and suboptimal healing capacity, predisposing both to fixation failure and non-union. Whereas a systemic osteoporosis treatment acts slowly, local release of osteogenic agents in osteoporotic fracture would act rapidly to increase bone strength and quality, as well as to reduce the bone healing period and prevent development of a problematic non-union. The identification of agents with potential to stimulate bone formation and improve implant fixation strength in osteoporotic bone has raised hope for the fast augmentation of osteoporotic fractures. Stimulation of bone formation by local delivery of growth factors is an approach already in clinical use for the treatment of non-unions, and could be utilized for osteoporotic fractures as well. Small molecules have also gained ground as stable and inexpensive compounds to enhance bone formation and tackle osteoporosis. The aim of this paper is to present the state of the art on local drug delivery in osteoporotic fractures. Advantages, disadvantages and underlying molecular mechanisms of different active species for local bone healing in osteoporotic bone are discussed. This review also identifies promising new candidate molecules and innovative approaches for the local drug delivery in osteoporotic bone.